PENERAPAN EKONOMI DIGITAL PADA PELAKU UMKM KABUPATEN BANGKALAN - Arisona, Dita; Anis, Moh; Indriani, Nurita (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
The COVID-19 pandemic has caused all activities to be carried out remotely, so that it greatly affects all kinds of aspects of life, not only public health and social life, but also education and economic conditions in Indonesia. This has caused the local government, especially Bangkalan Regency to implement a policy of Large-Scale Social Restrictions (PSBB), which of course is very influential for economic actors, one of which is MSMEs. The impact of this pandemic has affected MSME actors in Bangkalan Regency, especially MSMEs engaged in special foods and souvenirs. This is because the local government provides rules to close the tourism sector so that there are fewer domestic and international visitors visiting Bangkalan Regency. Therefore, many MSMEs have gone out of business during the COVID-19 pandemic. However, there are MSMEs that persist even though conditions do not allow for a COVID-19 pandemic, one of them is MSMEs, namely the Ambudi Makmur II Bangkalan Farmer Group. The MSMEs of the Ambudi Makmur II Farmer's Group in Bangkalan are innovative MSMEs but are unable to compete with competitors, this is due to the poor application of the digital economy to the MSMEs of the Ambudi Makmur Farmers' Group in terms of product marketing in e-commerce, causing the products to lose competitiveness with competitors. The location of the problem in this MSME is that the owner is not proficient in how to use e-commerce, for example in the form of product promotion, is less active in the use of e-commerce which causes the ordering process activities from customers to be constrained. Therefore, researchers want to provide training on how to use e-commerce properly so that these MSME products are not less competitive with competitors, considering that the MSMEs of the Ambudi Makmur Farmer Group have received a lot of appreciation from the district and national governments. This study uses a qualitative study with similar literature studies in order to obtain accurate results.